2015
DOI: 10.1063/1.4923426
|View full text |Cite
|
Sign up to set email alerts
|

Computational extended magneto-hydrodynamical study of shock structure generated by flows past an obstacle

Abstract: The magnetized shock problem is studied in the context where supersonic plasma flows past a solid obstacle. This problem exhibits interesting and important phenomena such as a bow shock, magnetotail formation, reconnection, and plasmoid formation. This study is carried out using a discontinuous Galerkin method to solve an extended magneto-hydrodynamic model (XMHD). The main goals of this paper are to present a reasonably complete picture of the properties of this interaction using the MHD model and then to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…2013). Extended-MHD simulations have previously demonstrated widening of MHD bow shocks around obstacles with size comparable to the ion inertial length, and this modification of the shock shape is associated with a suppression of the current in the postshock low density region by the Hall term (Zhao & Seyler 2015). However, it remains unclear if Hall effects can account for the observed shock anisotropy in the experimental bow shock, and future work will aim to investigate this with extended-MHD simulations.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2013). Extended-MHD simulations have previously demonstrated widening of MHD bow shocks around obstacles with size comparable to the ion inertial length, and this modification of the shock shape is associated with a suppression of the current in the postshock low density region by the Hall term (Zhao & Seyler 2015). However, it remains unclear if Hall effects can account for the observed shock anisotropy in the experimental bow shock, and future work will aim to investigate this with extended-MHD simulations.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…When ions and electrons decouple at the ion skin depth, the magnetic field is no longer frozen into the ion fluid, and two-fluid effects, in particular the Hall term in Ohm's law, may become important (Eastwood et al 2007;Shaikhislamov et al 2013). Extended-MHD simulations have previously demonstrated widening of MHD bow shocks around obstacles with size comparable to the ion inertial length, and this modification of the shock shape is associated with a suppression of the current in the postshock low density region by the Hall term j × B/en (Zhao & Seyler 2015). However, it remains unclear if Hall effects can account for the observed shock anisotropy in the experimental bow shock, and future work will aim to investigate this with extended-MHD simulations.…”
Section: Effect Of Magnetic Draping and Shock Anisotropymentioning
confidence: 99%
“…Perseus has been used previously to study the interaction of magnetised flows with obstacles. 16 Simulation results within 16 showed that the Hall term was important for the magnetotail structure behind the obstacles, but that it had no impact on the bow shock stand-off distance. Simulations of the present experiments using Perseus show qualitative agreement with the global structure of well-developed bow shocks.…”
Section: -7mentioning
confidence: 99%